Incidence of complications after laparoscopic and hysteroscopic surgeries for uterine myomas - N. K. Alizade (Акушерство, гинекология и репродукция, 2019)
Aim: to assess the incidence of complications after laparoscopic and hysteroscopic myomectomy.Materials and methods. The results of 378 laparoscopic and 292 hysteroscopic surgeries for uterine fibroids (myomas) have been retrospectively analyzed. All patients were examined for their history of gynecological and concomitant non-gynecological diseases, past surgeries, and the menstrual, sexual and reproductive functions. The patients underwent clinical blood analysis, urinalysis, electrocardiography and chest X-ray test, blood group and rhesus factor determination, hemostasis assay, blood analysis for RV, HIV and tumor markers, as well as transabdominal and transvaginal ultrasound using SSD-1200 and SSD-2000 devices (Aloka Ltd, Japan). We characterized the patients by the type of surgical intervention (laparoscopic or hysteroscopic), and also by age, indications for surgery, the number of fibroids and their locations, size of the uterus, presence of extragenital and genital disorders, and also by the surgery techniques. The post-surgery complication incidence rate was calculated and expressed as percentage (%), arithmetic mean (M), and standard error of the mean (m).Results. The overall incidence of severe postoperative complications did not differ between laparoscopic (2.7 ± 0.8 %) and hysteroscopic (2.1 ± 0.8 %) operations for uterine myomas (p > 0.05). The incidence of complications was significantly higher in women operated by laparoscopy if they underwent simultaneous operations (12.3 ± 4.0 % vs. 0.6 ± 0.4 % for non-simultaneous operations), if the number of fibroids was > 4 (3.9 ± 1.4 % vs. 1.1 ± 0.8 % in those with < 4 fibroids), in the presence of anemia (8.2 ± 2.9 % vs. 1.0 ± 0.6 % in cases with no anemia), and in patients with menstruation disorders (4.9 ± 1.8 % vs. 1.3 ± 0.7 % with normal menstruation). The operated patients significantly differed by the number of uterine fibroids: the average number of fibroids was larger in those operated laparoscopically (2.9 ± 0.05 vs. 2.3 ± 0.04; p < 0.01); the proportion of patients with 4 or more fibroids was also significantly higher in those patients (53.7 ± 2.6 % vs. 30.1 ± 2.7 %; p < 0.001). The compared groups also differed in the location of their myomas.Conclusion. The risk of postoperative complications after laparoscopic surgery is relatively high if simultaneous operations take place, if the number of fibroids is ³ 4, and in the presence of anemia or menstruation disorder.